Structural studies of the Fur protein from Rhizobium leguminosarum. (August 2002) - Kolade, O. O.; Bellini, P.; Wexler, M.; Johnston, A. W. B.; Grossmann, J. G.; Hemmings, A. M.
Abstract : The X-ray crystal structure of the apo-form of the Fur protein from Rhizobium leguminosarum has been solved at 2.7 å resolution. Small-angle X-ray scattering was used to give information on the solution conformation of the protein. The Fur homodimer folds into two domains. The N-terminal domain is formed from the packing of two helix-turn-helix motifs while the C-terminal domain appears primarily to stabilize the dimeric state of the protein.